The water level influence on biomass of Echinochloa polystachya (Poaceae) in the Jurumirim Reservoir (São Paulo, Brazil) - POMPÊO, M. L. M. [UNESP]; HENRY, R. [UNESP]; MOSCHINI-CARLOS, V. [UNESP] (Instituto Internacional de Ecologia, 2001)
Na zona de desembocadura do Rio Paranapanema, Reservatório de Jurumirim (23°27'-23°29'S e 48°39'-48°36'W, SP, Brasil), foi determinada mensalmente a biomassa of E. polystachya com oito quadros de 0,25 m² de agosto de 1993 a julho 1994. A variação sazonal da biomassa foi unimodal, com maior biomassa de novembro de 1993 a abril de 1994. A biomassa média determinada foi de 1.933,7 ± 479,5 gPS.m-2, com uma variação ao longo do ano de 1.149,0 a 2.755,9 gPS.m-2. A variação anual da biomassa verde aérea, detritos aquático e aéreo sugere que o principal período de crescimento de E. polystachya foi de dezembro de 1993 a maio de 1994, com pico entre fevereiro e março de 1994. Os dados demonstram que essa macrófita aquática está adaptada à variação do nível da água.

In the Paranapanema River mouth, Jurumirim Reservoir (23°27'-23°29'S and 48°39'-48°36'W, SP, Brazil), the biomass of E. polystachya was monthly determined with eight quadrats of 0.25 m² from August 1993 to July 1994. The seasonal variation in biomass was unimodal, with greater biomass from November 1993 to April 1994. The average biomass was 1,933.7 ± 479.5 gDW.m-2, with a variation along the year from 1,149.0 to 2,755.9 gDW.m-2. The annual variation of aerial green biomass, aerial and aquatic detritus suggest that the main growth period of E. polystachya was from December 1993 to May 1994, with peak between February to March 1994. The data indicate that this macrophyte is adapted to water level variation.
Influência do nível da água na biomassa de Echinochloa polystachya (Poaceae) no Reservatório de Jurumirim (São Paulo, Brasil)
Keywords: macrófita aquática; Echinochloa; biomassa; variação do nível da água; reservatório; Poaceae; macrophyte; Echinochloa; biomass; water level variation; reservoir; Poaceae